2023
DOI: 10.1029/2022jd037291
|View full text |Cite
|
Sign up to set email alerts
|

The Simulated Source Apportionment of Light Absorbing Aerosols: Effects of Microphysical Properties of Partially‐Coated Black Carbon

Abstract: Biomass burning (BB) fractions estimated with the aethalometer model differ from 0 even for pure aerosols from fossil fuel (FF) combustion. We used black carbon (BC) aerosols partially‐coated with non‐absorbing materials to represent typical FF aerosols, and the BB fractions were determined with the aethalometer model. Thus, the estimated BB fractions are the fractions that FF aerosols are incorrectly attributed to BB aerosols. The BC morphology and mixing state have significant effects on the estimation of BB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 73 publications
(141 reference statements)
0
12
0
Order By: Relevance
“…As the particle ages, BC may collapse to a more compact structure (Zhang et al, 2008;Lack et al, 2014;Peng et al, 2016;Bhandari et al, 2019). A larger D f has often been used to represent BC with more compact structure (Liu and Mishchenko, 2005;Kanngießer and Kahnert, 2018;Cheng et al, 2014;Luo et al, 2019Luo et al, , 2023Luo et al, , 2024. Previous studies have shown that aged BC can sometimes have a D f of about 2.3 -2.6, assuming a fractal structure for aged BC (Adachi et al, 2010(Adachi et al, , 2007Chen et al, 2016).…”
Section: Bc Morphological Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…As the particle ages, BC may collapse to a more compact structure (Zhang et al, 2008;Lack et al, 2014;Peng et al, 2016;Bhandari et al, 2019). A larger D f has often been used to represent BC with more compact structure (Liu and Mishchenko, 2005;Kanngießer and Kahnert, 2018;Cheng et al, 2014;Luo et al, 2019Luo et al, , 2023Luo et al, , 2024. Previous studies have shown that aged BC can sometimes have a D f of about 2.3 -2.6, assuming a fractal structure for aged BC (Adachi et al, 2010(Adachi et al, , 2007Chen et al, 2016).…”
Section: Bc Morphological Modelmentioning
confidence: 99%
“…We used the tunable algorithm developed by Woźniak (2012), which accurately reproduces the fractal law, to generate the fractal BC aggregates. Then, the coating materials were added similarly to previous studies (Zhang et al, 2018;Luo et al, 2023Luo et al, , 2024. We assumed that the coating structure is spherical.…”
Section: Bc Morphological Modelmentioning
confidence: 99%
See 3 more Smart Citations